"I really wanted to do it better this year": how cognitive coaching alters self-efficacy and changes classroom writing instruction - Dixon, Robin Michelle (My University, 2025)
This dissertation investigates the impact of prior writing experiences to determine their effects on teachers’ self-efficacy as writers and writing teachers and on classroom practice. Additionally, the study explored whether cognitive coaching altered teachers’ self-efficacy. Using qualitative action research, the study placed personal experience at the forefront of research analysis to determine if cognitive coaching altered efficacious beliefs and classroom practice. The data collection methods were four phenomenological semi-structured interviews, four cognitive coaching cycles, and participants’ reflective journals. The study aimed to answer the following two research questions. First, in what ways do elementary teachers’ writing identities inform their writing instruction (self-perceptions)? Second, how does cognitive coaching enable teachers to understand and adapt their self-efficacy as writing teachers? Ultimately, the study answered both research questions. The findings indicate that cognitive coaching successfully alters self-efficacy beliefs and positively impacts classroom practice. Findings also proved that Bandura’s sources of efficacy do alter self-efficacy beliefs. The study also discounted Bandura’s belief that low efficacy beliefs hinder people from continuing in a task or endeavor. This research contributes to understanding why elementary teachers may or may not teach writing in their classrooms and determines how to positively influence the scope and nature of writing instruction in classrooms. Future implications of the study include using cognitive coaching as a sustainable, ongoing form of professional development. Additionally, the study has implications for altering efficacy and practice for other curricular areas, not just writing.
Keywords: Cognitive coaching; Self-efficacy; Social Cognitive Theory; Changes in teacher writer self-efficacy; Altering writer self-efficacy; Sources of self-efficacy